Adopting Self-Directed Learning as an Approach for Enhancing Academic Achievement of University Students - Kanyopa, Theresia Joakim; Makgalwa , Matseliso Mokhele (Journal of Ecohumanism, 2024)
The prevalence of self-directed learning (SDL) has increased significantly, contributing to crucial online learning platforms. SDL is an online learning platform in higher education that has ignited a transformation in the way students and lecturers interact and how they access educational resources. This study explored the use of SDL in higher education contexts to enhance students’ academic achievements within the digital realm. The study employed an interpretive qualitative case study approach to explore the influence of SDL on students’ learning experiences and their academic achievements. Focus group discussion and reflective essay writing were used to generate data that were thematically analysed. SDL was used to frame the study to explore the intrinsic and extrinsic motivations that were used as drivers for adopting SDL to enhance the academic achievements of university students. The study found that SDL significantly enhances students’ academic achievements by fostering active engagement, learning autonomy and self-regulation in contemporary higher education contexts. The study also emphasises the contribution of SDL to students’ academic achievement, ultimately leading to improved institutional status.